2016
DOI: 10.14639/0392-100x-1279
|View full text |Cite
|
Sign up to set email alerts
|

Ricostruzione multiplanare 3D di immagini cone beam per l’idenficazione della posizione degli impianti cocleari. Studio su ossi temporali e pazienti impiantati

Abstract: Questo studio riporta un’analisi retrospettica delle immagini cone beam CT effettuate su 8 pazienti adulti sottoposti ad impianto cochleare MedEl flex 28 e su 14 ossi temporali impiantati con lo stesso tipo di array portaelettrodi. Lo scopo dello studio é di determinare l’affidabilità della metodica cone beam CT nella valutazione della posizione intracocleare degli elettrodi in impianti che si posizionano lungo la parete laterale del lume cocleare, quindi non perimodiolari la cui posizione é più facilmente ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A precise preoperative measurement of the CDL can facilitate the selection of an appropriate electrode array for each cochlea (5,13,17,18). In addition, the knowledge of the individual anatomy and length of the cochlea is critical for avoiding insertion failure of the CI electrode; plus accurate CDL values can also result in improvement of the audiological outcome by allowing for more precise adjustment of the frequency distribution (19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A precise preoperative measurement of the CDL can facilitate the selection of an appropriate electrode array for each cochlea (5,13,17,18). In addition, the knowledge of the individual anatomy and length of the cochlea is critical for avoiding insertion failure of the CI electrode; plus accurate CDL values can also result in improvement of the audiological outcome by allowing for more precise adjustment of the frequency distribution (19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis CDL measurements were performed with 3D-curved multiplanar reconstruction (MPR) of the imaging dataset as described in previous publications (7,9,(12)(13)(14). A manually placed Bézier path with a close approach to the lateral wall of the cochlear duct using the DICOM Medical Image Viewer Horos (Version 3.3.5; Nimble Co LLC d/b/a Purview, Annapolis, MD) was created in the imaging dataset.…”
Section: Imagingmentioning
confidence: 99%
“…Therefore, a new trauma grading applicable for imaging should be developed. Mosnier et al (9) and De Seta et al (8) used a simplified trauma staging (no trauma; dislocation) in their image-based studies. Accordingly, our study supports the feasibility of micro-CT for trauma assessment, with nearly the same accuracy as histology.…”
Section: Discussionmentioning
confidence: 99%
“…Cone-beam computed tomography (CBCT) has established its position as a clinical modality for postoperative CI imaging. It has also been applied for CI studies in TB (8)(9)(10)(11). Several studies have shown that the accuracy of trauma assessment can be significantly improved with the image fusion technique of preimplant and postimplant CBCT images (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The full insertion of electrodes would be required to bring the stimulation contacts closer to the modiolus wall. Frijns et al found no correlation between the distance to the modiolus and the threshold or the maximum levels with a straight lateral wall electrode [20,21,22].…”
Section: Sturm Affirmed That In Children With Normal Ears Consonant-mentioning
confidence: 98%